2016
DOI: 10.1149/07401.0037ecst
|View full text |Cite
|
Sign up to set email alerts
|

Li-Ion Battery Charging Efficiency

Abstract: The main objective of this article is determination of the charging and discharging efficiency of the Li-ion battery depending on the value of the charging and discharging current. An automated workplace allows us to measure the capacity of cells, temperature and other parameters required for assessing the performance of batteries. A dependence of the energy storage efficiency on the charging and discharging current was found out. Consequently this measured dependence was approximated with an analytical expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…This factor also depends on the battery chemistry, configuration or age. In the battery models used in this work, the ohmic losses are explicitly taken into account separately, and the value for the efficiency was taken from literature (Toman et al , 2016; Yang et al , 2018) as a way of compensating for the secondary above-mentioned effects. Values in the literature range from 90% to above 99% thus some exploration on this parameter was performed.…”
Section: Sensitivity Studiesmentioning
confidence: 99%
“…This factor also depends on the battery chemistry, configuration or age. In the battery models used in this work, the ohmic losses are explicitly taken into account separately, and the value for the efficiency was taken from literature (Toman et al , 2016; Yang et al , 2018) as a way of compensating for the secondary above-mentioned effects. Values in the literature range from 90% to above 99% thus some exploration on this parameter was performed.…”
Section: Sensitivity Studiesmentioning
confidence: 99%
“…The battery efficiency is a function of the battery temperature, charging or discharging load, and the current SoC [16,17]. An average charge and discharge efficiency of 0.98 and 0.99 are assumed, respectively [18,19].…”
Section: The Batterymentioning
confidence: 99%
“…The constraints in Eq. (17) provides safety limits of the battery discharging and charging power. Since the charging process is aimed to be controlled by another control element (not by the DC-DC boost converter of the FC), the constraint P min B is neglected in this study.…”
Section: Cost Function and Constraintsmentioning
confidence: 99%
“…Applying high voltages to the conventional batteries shortens the charging period to several tens of minutes, although consequently causing the unfavorable energy (voltage) loss, self-heating, and degradation of battery components. 4,5 Former studies revealed that optimizing the crystal structures of the electrode-active materials, controlling the nanoscale geometry, and addition of nanocarbons such as graphene were effective to achieve the outstanding charge/discharge rates over 10−100 C (x C corresponds to a rate to fully charge/discharge a cell in 1/ x hours). 6−9 Still, most of the newly developed materials are yet to be commercialized because of the strict criteria for practical use, such as cyclability, energy density, voltage, reliability, toxicity, and mass producibility.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In response to the rapid development of electric vehicles and portable electronic devices, accelerating the charging/discharging rates of lithium-ion batteries has become one of the most critical issues, in addition to increasing energy density. For instance, the required time to fully charge the car batteries, typically 1–3 h, should hopefully be shortened to be compared with that for filling up petrol motor cars in several minutes. Applying high voltages to the conventional batteries shortens the charging period to several tens of minutes, although consequently causing the unfavorable energy (voltage) loss, self-heating, and degradation of battery components. , Former studies revealed that optimizing the crystal structures of the electrode-active materials, controlling the nanoscale geometry, and addition of nanocarbons such as graphene were effective to achieve the outstanding charge/discharge rates over 10–100 C ( x C corresponds to a rate to fully charge/discharge a cell in 1/ x hours). Still, most of the newly developed materials are yet to be commercialized because of the strict criteria for practical use, such as cyclability, energy density, voltage, reliability, toxicity, and mass producibility.…”
Section: Introductionmentioning
confidence: 99%